Формування сценаріїв управлінської діяльності на основі дослідження інформаційного простору - Бойченко, А.В.; Ланде, Д.В. (Реєстрація, зберігання і обробка даних, 2017)
Розглянуто технологічні рішення, що дозволяють аналізувати масиви повнотекстових документів, і запропоновано процедуру автоматизованої побудови сценаріїв управлінської діяльності на основі аналізу інформаційного простору для вибраних предметних областей. Рассмотрены технологические решения, позволяющие анализировать массивы полнотекстовых документов, и предложена процедура автоматизированного построения сценариев управленческой деятельности на основе анализа информационного пространства для выбранных предметных областей. It is considered the development of a scenario approach and the construction of an information technology, which allows in an automated mode, based on the analysis of the input documentation package, to solve the problem of the formation and ranking of scenarios of influencing the objects that correspond to the selected key concepts.A mathematical model of qualitative estimation of management activity scenarios for a subject area is worked out. To construct a scenario, an abstract automaton is proposed that describes the requirements based on the description of the analytic task. The scenarios are singled out from the semantic network. There are the vertices of concepts, and the arcs to be mutual relations, for example, «cause – consequence». A modified ant colony optimization (ACO) approach for forming scenarios is proposed. To check out the suggested technology, text domains were created for such subject areas as «Brexit», «Mass Shuting», «Catalan referendum», «Saudi Arabian purge», «Zimbabwean coup d’etat», «Syrian civil war».